The Association Between Documentation of Koplik Spots and Laboratory Diagnosis of Measles and Other Rash Diseases in a National Measles Surveillance Program in Japan - Kimura, Hirokazu; Shirabe, Komei; Takeda, Makoto; Kobayashi, Miho; Tsukagoshi, Hiroyuki; Okayama, Kaori; Ryo, Akihide; Nagasawa, Koo; Okabe, Nobuhiko; Minagawa, Hiroko; Kozawa, Kunihisa (Frontiers in Microbiology, 2019)
Koplik spots are considered a disease-specific sign for measles, although comprehensive virological studies have not been conducted to date. In Japan, a national survey of 3023 measles and measles-suspected cases was conducted between 2009 and 2014 using polymerase chain reaction (PCR) or reverse transcription PCR (RT-PCR) to detect various rash/fever-associated viruses. Koplik spots were observed in 717 of 3023 cases (23.7%). Among these, the measles virus was detected in 202 cases (28.2%), while the rubella virus was detected in 125 cases (17.4%). Other viruses were detected in 51 cases having the spots (7.1%). In some of the cases with spots, two or three viruses, such as the rubella virus, parvovirus, and human herpesvirus type 6 were also detected. The sensitivity and specificity of Koplik spots as a diagnostic marker for measles were 48 and 80%, respectively. The results suggested that Koplik spots might appear not only in measles but also in other viral infections, such as rubella, as a clinical sign.